Regulation of gene expression in brain and liver by marine n-3 polyunsaturated fatty acids - Kaur, G.; Sinclair, A. J. (Progress in Nutrition, 2010)
SummaryPolyunsaturated fatty acids (PUFA) can affect gene expression through changes in membrane composition and signalling, eicosanoid production, oxidant stress, nuclear receptor activation or covalent modification of specific transcription factors. This paper considers the effects of marine n-3 PUFA on expression of genes involved in various pathways and in brain and liver. Increasing the n-3 PUFA content of the diet of rats induces changes in the expression of more than 100 genes in the brain, involved in synaptic plasticity, cytoskeleton, signal transduction, ion channel formation, energy metabolism and regulatory proteins. Further work has revealed an interaction between zinc and docosahexaenoic acid (DHA) in brain (in vivo & in vitro). In the liver, studies suggest that marine n-3 PUFA are involved in the suppression of glycolytic and lipogenic genes, and as activators of fatty acid oxidation at the level of gene expression to control mitochondrial and peroxisomal lipid metabolism.Regolazione dell’espressione genica nel cervello e nel fegato da parte di acidi grassi n-3 polinsaturi di origine marinaRiassuntoGli acidi grassi polinsaturi (PUFA) possono influenzare l’espressione genica modificando la composizione di membrana e la trasmissione del segnale: produzione di eicosanoidi, stress ossidativo, attivazione di recettori nucleari, modifica covalente di specifici fattori di trascrizione. Questo studio considera gli effetti di n-3 PUFA di origine marina sull’espressione di geni coinvolti nei diversi pathways, nel cervello e nel fegato. Aumentare il contenuto di n-3 PUFA nella dieta dei ratti induce cambiamenti nell’espressione di oltre 100 geni nel cervello, coinvolti nella plasticità sinaptica, citoscheletro, trasduzione del segnale, formazione di canali ionici, metabolismo energetico e proteine regolatrici. Ulteriori studi hanno rivelato una interazione tra zinco e acido docosaesaenoico (DHA) nel cervello (in vivo e in vitro). Nel fegato, gli studi suggeriscono che n-3 PUFA di origine marina sono coinvolti nella sopressione della lipogenesi, e come attivatori dell’ossidazione di acidi grassi a livello di espressione genica nel controllo del metabolismo lipidico mitocondriale e perossisomiale.